From the streets to the feeds into parliament: The role of digital media within the feminist social movement un violador en tu camino - Stielow, Julia Marie (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
The feminist social movement Un Violador En Tu Camino (Un Violador) emerged amidst civil unrest in Chile in 2019. It addresses systemic oppression faced by women, lesbians, trans, and non-binary individuals (WLINTA*). This thesis delves into the role of digital media within the movement, investigating the impact of digital and specifically social platforms on the dynamics and outcomes of the movement. Drawing upon Digital Media, Political, and Feminist Studies, this research examines how digital platforms shaped Un Violador’s evolution, visibility, and political engagement. This work reveals a nuanced relationship between Un Violador en Tu Camino and digital media, highlighting both empowering and constraining aspects. While digital platforms facilitated global visibility, informal networking, and political influence, they also imposed barriers to access and reinforced patriarchal structures. Through an intersectional feminist lens, this thesis sheds light on the complexities of digital media involvement in feminist activism, challenges celebratory narratives and emphasizes the need for critical examination. The findings specifically underscore the importance of addressing digital inequality and advancing inclusive digital activism. Future research directions include comparative analyses with other feminist movements and exploring the movement’s dynamics from different cultural contexts. Ultimately, this research contributes to advancing feminist activist politics and promoting the empowerment of WLINTA*, signaling a promising avenue for closing gender gaps and digital disparities.
Keywords: Feminism; Digital Media; Internet; Activism; Protest; 300 Sozialwissenschaften